Reliability engineering and risk analysis - Modarres, M. (Mohammad) (Marcel Dekker, 1999)
An introduction and explanation of pragmatic methods and techniques for reliability and risk studies, and a discussion of their uses and limitations. It features computer software that illustrates numerous examples found in the book, offering to help engineers and students solve problems. There is a module on Bayesian estimation.